Molecular and immunological profiling of Bartonella spp. in shelter cat population in Peninsular Malaysia - Alias, Nurul Najwa Ainaa (2021)
Feline bartonellosis is a zoonotic disease caused by Bartonella henselae which may result in either mild or severe bacteremia in asymptomatic cats. Severe human infections such as cat scratch disease (CSD), endocarditis, and ocular bartonellosis have been associated with infections due to Bartonella spp. including Bartonella henselae. To date, no biosurveillance and immunological profiling in Bartonellapositive shelter cats have been conducted in Malaysia. A molecular prevalence study carried out in 2017 confirmed that 16.9 % (48/284) pet cats in Selangor, Malaysia were positive with B. henselae. However, this study was performed only on pet cats and represents a small cohort of cat population in Malaysia. Shelter environment remains as prime sources where emerging pathogens could arise as the result of mixing of animals from various origins; therefore, giving the possibility of inadvertent disease transmission between shelter cats to community cats and also human especially those with immunocompromised status. Therefore, this study was aim to determine the molecular, serological prevalence of Bartonella spp. in shelter cats, immunophenotyping of CD4 and CD8 as well as the association between each assay and also association with physical examination findings. Overall, blood was collected from 217 cats, flea from 100 cats and oral swabs from 176 cats were subjected to molecular analysis. A total of 122 serum collected were subjected to serological detection of IgM and IgG while 110 whole blood that were kept in -80°C freezer were subjected for immunophenotyping of CD4 and CD8. Molecular detection of Bartonella DNA was performed using conventional PCR detecting 16S-23S rRNA intergenic spacer sequence which yield a single band at 630 to 680 base pair. Bartonella DNA was detected from four cats (4/217;1.8%) in which three from cat’s blood and one from oral swab. Meanwhile, 8.0% (8/100) Bartonella DNA were detected in flea from 100 cats. All the positive amplicon were sent for sequencing. Sequence analysis of the 16S- 23S rRNA intergenic spacer gene fragments show the identification of B. henselae in blood (n=3), oral swab (n=1) and flea from one cat, B. koehlerae from one flea and B. clarridgeiae from six fleas. The sequence analysis reveals high sequence similarity of 98.7% with B. henselae, 97.9% B. koehlerae and 97.8%-100.0% with B. clarridgeiae respectively. Phylogenetic tree constructed based on Bartonella 16S-23S rRNA intergenic spacer gene sequences revealed a close genetic relationship between Malaysian B. hensalae strains from blood and oral swab samples with B. henselae of Korea and China strains while genetic relationship from flea samples were closely related with B. henselae from China strain, B. koehlerae from Palestine strain, and B. clarridgeiae from China and Australia strains. Of 122 cats with serum samples available for testing using IgM and IgG commercial indirect immunofluorescence assay (IFA) against B. henselae, 82.8% (101/122) cats demonstrated seroreactivity to B. henselae antigen. A total of 47.5% (58/122) cats were positive for IgM antibody alone, 65.6% (80/122) cats were positive for IgG antibody alone and 30.3% (37/122) were positive for both IgM and IgG. In addition, immunophenotyping of 110 frozen whole blood detecting CD4 and CD8 T cells were performed. Results showed that 60.0% (66/110) cats had abnormal ratio of CD4 to CD8. Only one cat was positive for both PCR and antibody assays against Bartonella spp. had abnormal CD4:CD8; however, it did not show any clinical signs. Statistical analyses suggested there were no association between PCR, serological test and CD4:CD8. Next, a survey on shelter management practices and their personnel awareness towards bartonellosis were also conducted by distributing a set of questionnaires to the shelter personnel. Surveys from management practices of shelter cats revealed that five out of ten shelters were practicing ectoparasite control and 93.3% (28/30) shelter’s personnel were aware that cat and cat flea might contribute to zoonotic diseases. However, they were unaware about Bartonella can infect human and cat scratch disease (CSD). The high B. henselae seroreactivity among shelter cats with low molecular detection rate suggests previous infection or low bacteraemia level that was not detectable by conventional PCR analysis. In addition, this study observed the presence of more than one species in cat’s fleas, while only B. henselae was detected in the cat hosts. As there were no clear symptoms and diagnostic markers that can be used to determine the status of Bartonella infection among cats, this may pose zoonotic risk to children, elderly and immunocompromised individual who are more susceptible to Bartonella infection.